Research on collapse failure characteristics and theoretical prediction formulas of Solid expandable tubular. (March 2022) - Zhu, Xiaohua; Cheng, Feilong; Shi, Changshuai; Chen, Kailin; Tan, Ling
Highlights: The collapse strength of SET after expansion is reduced by 15%-30%. The wall thickness has almost a linear effect on the collapse performance. A 20G collapse prediction formula with a Dexp/t ratio less than 30 is obtained. Abstract: Solid expandable tubular (SET) is plastically formed in the well, it needs to undergo the double test of internal and external pressure. The collapse resistance of the SET after expansion is an important guarantee for the wellbore structural integrity reconstruction. In addition, due to the diversity of the material of the SET and the complexity of plastic forming, there is no unified formula for calculating the collapse strength of the SET. Aiming at the above problems, this paper builds a three-dimensional dynamic collapse strength calculation Finite element model (FEM) based on the collapse experiment of SET, and analyzes the influence of expansion rate, wall thickness and eccentricity on the collapse strength of expansion pipes, and fits the theoretical calculation formula of collapse strength. The research results show that: the expansion rate causes the collapse performance of the pipe after expansion to be reduced by 15% to 30%; the wall thickness has almost a linear effect on the collapse performance; the greater the eccentricity, the lower the collapse strength, the more likely it is to " Concave ". Through data fitting, a theoretical prediction formula for the collapse strength of SET with a material of 20G and a diameter-to-thickness ratio of less than 30 is obtained. The formula is simple and easy to calculate using parameters. The research results in this paper provide theoretical guidance and methods for the study of the collapse strength of SET.